Cooperation of client routines in client-server network architecture without using of special monitor routine on server - Dimov, Peter (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1997)
A method for communication between client routines without monitoring by a special routine, working on a server, is proposed. The base of the method is a message transferring engine, but not in the classical form. The method is oriented to data sharing between computers in a client-server architecture network. All data are stored on a PC disk space and there is no need to store data on the server. The server is used only for files lock and unlock purposes and its disk capacity is used only as an intermediate storage. The method ensures higher information security level than the traditionally used methods. Communication between computers allows to develop applications for cooperative work and documents routing. In a more global aspect the described engine is applicable in both single and multiprogram environments.